Estimating epiphytic lichen richness by single families in Mediterranean forests - Aragón, Gregorio; Belinchón, Rocío; Martínez, Isabel; Prieto, Maria (Forest Ecology and Management, 2013)
The current trend of declining epiphytic richness caused by human activities (forest fragmentation, log- ging, agriculture, and livestock grazing) and the greater efforts required to sample and identify the most inconspicuous species have necessitated the use of indicators of the species richness. In this study, we examined the potential of predicting epiphytic lichen richness based on the richness of a single taxon (fam- ily) of the most conspicuous lichens (macrolichens) in Mediterranean woodlands. Since our working hypothesis is that the richness of some conspicuous elements is tightly connected with the total richness, we expect this connection is maintained even after composition shifts (for instance composition changes between coniferous and oak forests). In order to control the large set of confounding factors at macro- and microclimate scales our present study was conducted in 504 forest stands, which represented awide range of Mediterranean climates, management intensity levels, canopy cover types, and tree sizes. The presence/ absence of epiphytic lichens were determined in 7560 trees, which were dominated by coniferous (Pinus nigra and P. sylvestris) and oak (Quercus ilex ssp. ballota, Q. faginea, and Q. pyrenaica) species. In oak forests, the increased richness of Collemataceae and the complex known as ‘‘rest of Peltigerales’’ was followed by an increase in the overall epiphytic richness, whereas there was a strong positive correlation between Par- meliaceae and total epiphytic richness in coniferous forests. In both cases, the richness of these predictors increased in well-preserved forest stands with dense canopies. Thus, we propose the potential use of Par- meliaceae (for coniferous forests) and the Collemataceae and the ‘‘rest of Peltigerales’’ (for oak forests) as indicators in the Mediterranean region because they have a cosmopolitan distribution, grow in a wide range of environmental conditions, and are correlated with changes in the epiphytic richness caused by for- est disturbances. ?
From Duplicate 2 ( Estimating epiphytic lichen richness by single families in Mediterranean forests - Aragón, Gregorio; Belinchón, Rocío; Martínez, Isabel; Prieto, Maria )From Duplicate 2 ( Estimating epiphytic lichen richness by single families in Mediterranean forests - Aragón, Gregorio; Belinchón, Rocío; Martínez, Isabel; Prieto, Maria )
Keywords: epiphytic lichens; Forest structure; Indicator species; Mediterranean; Species richness

Effects of forest management on epiphytic lichen diversity in Mediterranean forests - Aragón, Gregorio; Martinez, I.; Izquierdo, P.; Belinchon, R.; Escudero, A. (APPLIED VEGETATION SCIENCE, 2010)
Question What are the responses of epiphytic lichens to the intensity of management along a large environmental gradient in Mediterranean Quercus forests? Location Central Spain. Methods This study was carried out on 4590 trees located in 306 forest stands dominated by Quercus faginea or Quercus ilex ssp. ballota. The effect of forest management and other predictor variables on several species diversity indicators were studied. Variables modelled were total species richness, cyanolichen richness and community composition. A large number of predictor variables were included: forest fragmentation (patch size, stand variability), climate and topographic (altitude, slope, sun radiation, annual rainfall and mean annual temperature) and intensity of management. General linear models and constrained ordination techniques were used to model community traits and species composition, respectively. Results Total richness and especially cyanolichens richness were significantly and negatively affected by the intensity of management. Lichen composition was influenced by management intensity, climatic and topographic variables and stand variability. Conclusions In Mediterranean forests, human activities related to forestry, agricultural and livestock use cause impoverishment of lichen communities, including the local disappearance of the most demanding species. The conservation of unmanaged forests with a dense canopy is crucial for lichen diversity.
The following values have no corresponding Zotero field: pub-location: COMMERCE PLACE, 350 MAIN ST, MALDEN 02148, MA USA publisher: WILEY-BLACKWELL PUBLISHING, INC
Keywords: Community traits; Cyanolichens; Drivers of composition; fragmentation; land use; oak forests; Spain; Variation partitioning

Effects of Mediterranean dehesa management on epiphytic lichens. - Aragón, Gregorio; López, Rubén; Martínez, Isabel (The Science of the total environment, 2010)
Spanish holm oak (Quercus ilex subsp. ballota) open woodlands (dehesas) maintain a high diversity of plants and animals compared to other forested Mediterranean habits, but little is known about the responses of epiphytic lichens to different management regimes that are applied to this woodland type. The present study was carried out in central-southern Spain and included four management regimes: agriculture, grazing of sheep, grassland grazed by wild ungulates (deer), and abandoned dehesas covered by shrubs. Total species richness and cover exhibited considerable variation among management regimes. Both parameters tended to decrease with the intensity of management, abandoned dehesas maintaining a higher number of species than more intensively managed habitats. Lichen composition also significantly differed among the four regimes. Nitrophytic species were clearly associated with more intensive management regimes (farming or livestock management), whereas non-nitrophytic species favored abandoned dehesas.
The following values have no corresponding Zotero field: publisher: Elsevier B.V. accession-num: 20937519
Keywords: Lichen composition; Mediterranean Spain; Nitrophytic specie; Open woodlands; quercus ilex subsp. ballota; s Management regime